Capital Expenditure, Audit Opinion and Fiscal Autonomy under Fiscal Decentralization: Evidence from Indonesian Provinces - Putri, Amelia Hamdani; Mile, Yuldi; Betty, Betty; Widyakusuma, Annastry (International Ecsis Association, 2026)
Despite the expansion of fiscal decentralization in Indonesia, provincial governments remain structurally dependent on central government transfers, raising concerns about the substantive achievement of fiscal autonomy. However, prior research largely conflates compliance-based accountability indicators with development-oriented fiscal mechanisms, leaving underexplored how capital expenditure and audit opinion differentially shape fiscal independence. This study aims to examine the distinct roles of capital expenditure and audit opinion in explaining provincial fiscal autonomy under an agency theory framework. Using secondary data from 34 Indonesian provinces over the period 2021–2023 (102 observations) and employing multiple linear regression analysis, this paper tests the effects of development-oriented fiscal allocation and compliance-based monitoring on the fiscal independence ratio. The findings indicate that capital expenditure has a positive and significant effect on fiscal autonomy, suggesting that discretionary investment in infrastructure and public assets enhances long-term revenue capacity. In contrast, audit opinion exhibits a significant but negative association, indicating that compliance with reporting standards does not necessarily translate into stronger fiscal independence. These results highlight the conceptual distinction between monitoring mechanisms and fiscal discretion in decentralized systems. This study contributes to public sector accounting and fiscal decentralization literature by clarifying that accountability compliance and development-oriented fiscal decisions operate through different mechanisms in shaping regional financial performance. Practically, the findings inform policymakers to integrate audit-based evaluations with strategic capital allocation in advancing sustainable fiscal autonomy.